2014
DOI: 10.1088/1009-0630/16/2/11
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of First Wall Materials in a Magnetically Confined Fusion Device by Polarization-Resolved Laser-Induced Breakdown Spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS) is a powerful analytical tool for realtime diagnostics and detection of multiple elements deposited at the first wall of magnetically confined plasma fusion devices. Recently, we have tested LIBS in our laboratory for application to in situ real-time diagnostics in the fusion device EAST. In this study, we applied polarizationresolved LIBS (PR-LIBS) to reduce the background continuum and enhance the resolution and sensitivity of LIBS. We used aluminium (Al) (as a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
(25 reference statements)
0
15
0
Order By: Relevance
“…Since the 1960s [9], laser-induced breakdown spectroscopy (LIBS) has become a significant tool for component identification on various kinds of samples like metals, alloys [10][11][12][13][14][15]. It has been developed as an analysis technique for the first wall and the region near the diverter in fusion devices such as EAST due to the lower cost, little damage, and no need for pre-treatment [15][16][17][18][19]. Recently, most corresponding studies were carried out by experimental techniques [12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s [9], laser-induced breakdown spectroscopy (LIBS) has become a significant tool for component identification on various kinds of samples like metals, alloys [10][11][12][13][14][15]. It has been developed as an analysis technique for the first wall and the region near the diverter in fusion devices such as EAST due to the lower cost, little damage, and no need for pre-treatment [15][16][17][18][19]. Recently, most corresponding studies were carried out by experimental techniques [12,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Laser induced breakdown spectroscopy (LIBS) is a promising analytical method in many fields [1][2][3][4][5][6][7]. This technique is a type of optical emission spectroscopy that uses a laser pulse as the excitation source.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is the observation that the continuum emission from a laser plasma tends to be more polarised than the line emission [1][2][3] which is useful for analytical techniques such as Laser Induced Breakdown Spectroscopy (LIBS). In previous studies, the degree of polarisation (P) of the light emitted from a laser produced plasma was measured for various focal positions, 1,4 laser energies, 4,5 background pressures, 5,6 incident laser polarisations, 3,4 detection directions, 4,6 and pulse durations. 1,6 In many cases, the use of a polariser in front of the spectrometer during a LIBS measurement suppressed the continuum and improved the limit of detection (LOD) by increasing the signal to background ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the degree of polarisation (P) of the light emitted from a laser produced plasma was measured for various focal positions, 1,4 laser energies, 4,5 background pressures, 5,6 incident laser polarisations, 3,4 detection directions, 4,6 and pulse durations. 1,6 In many cases, the use of a polariser in front of the spectrometer during a LIBS measurement suppressed the continuum and improved the limit of detection (LOD) by increasing the signal to background ratio. In one study, 7 it was found that no significant polarisation of either the continuum or line emissions could be observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation